SIGNIFICATIONS FROM YOUNG UNIVERSITY STUDENTS ABOUT HUMAN RIGHTS - Magendzo K, Abraham (2019)
This article gives an account of the main results of an investigation about meanings attributed by a group of university students to human rights in Chile. Among the results, it is possible to advance that young people express a favorable position with respect to some principles related to human rights, such as freedom of belief, equality and respect for diversity, the role of the State as guarantor of rights, among others. Along with this, new elements are incorporated into the discussion, based on three central categories that cross similar research at the international level, which can be grouped into: pedagogical practices, educational management, social justice and inclusion. In each of them, in turn, reference will be made to three intervening variables in human rights education: cognitive, affective-behavioral and contextual.